KONSEP HABLUMMINALLAH DALAM LIRIK LAGU SANDARAN HATI LETTO - Eka Anjani; Fenny Mahdaniar (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The Song is a narrative literary work, as well as an effective communication medium. That’s because song can express notions and feelings and can last a long time. Not infrequently, songs are used as a means for musicians to convey da'wah messages. However, sometimes the language used by musicians does not always express explicit but implicit intentions, such as the Letto song